Islamic Banking and Sharī‘ah Scholars in Nigeria - Kewuyemi, Kareem Muritala (The Journal of Rotterdam Islamic and Social Sciences, 2016)
Compliance with Sharī‘ah rules is compulsory for all Islamic banks; and such compliance is monitored by Sharī‘ah scholars. Therefore, this article examines and gauges the level of understanding of Nigerian Sharī‘ah scholars (the custodians of Sharī‘ah rules in the country) and their perceptions of the Islamic banking and its rules particularly interest (ribā). The survey method involving the use of purposive sampling was adopted to administer 1,040 copies of a questionnaire sent to Nigerian Sharī‘ah scholars, though some key people were also interviewed. The questionnaire, which contains 19 items, was designed to elicit information from them on issues such as their understanding of ribā, its uses in the Qur’an, Islamic banking products, collateral security and promotion (promos). Our findings revealed that there were more respondents (917) who considered usury to be forbidden than those who considered (871) interest to be forbidden. A large number of Sharī‘ah scholars (93.6%) confused interest with usury which suggests that both interest and usury refer to ribā. Some believed that ribā (48.6%) only refers to usury, while most of the respondents (74.1%) opined that all forms of interest are prohibited. About 73.7%, 86.3%, and 27.6% of the respondents believed rahn (collateral security), innovating interest-free financial products and patronising conventional banks respectively were allowed. The Sharī‘ah scholars surveyed (64.7%) believed that conventional financial products can be made Sharī‘ah-compliant, banks can operate successively without interest (89%), and they (70.3%) were of the views that promotions done by the conventional banks are against the teachings of Islam considering the source of the funds used in their promotions which contains the accrued interest income and lack of fairness in the distributions of the promotions. Seminars, workshops, and conferences can be organized for the scholars with a view to training them in the areas of Islamic banking and finance. Collaboration can be established between the Nigerian Sharī‘ah scholars and the Sharī‘ah scholars from the Middle East so that the former can benefit from the wealth of experience of the latter in the areas of Islamic banking and finance.